Data Mining Association Rules Menggunakan Algoritma Apriori untuk Menemukan Pola Pembelian Wisatawan pada Pasar Seni Guwang Bali - Pratama, I Putu Agus Eka (LPPM POLITEKNIK LP3I BANDUNG, 2023)
As one of the art markets of interest to tourists, the Guwang Art Market in Gianyar Regency, Bali, has purchased transaction data that has not been utilized optimally to help traders understand consumer purchasing patterns and the relationship between items as a basis for decision making. For this reason, in this research, DAMIARPRI was designed and implemented as a web-based system using Data Mining Association Rules and the Apriori Algorithm to manage consumer purchasing transaction data at the Guwang Art Market. This research uses the Design Science Research Methodology (DSRM) research methodology, with case study qualitative research methods, as well as the BlackBox Testing testing method. The research results show that the system can show information on consumer purchasing patterns and the relationship between items, where the items most frequently purchased by tourists are men's beach pants, followed by men's beach t-shirts and men's beach sandals, with a support value of 3% and confidence of 100%. Based on this, traders at the Guwang Art Market can make decisions to add these items to increase income. In the future, it is hoped that the system can be further developed according to user needs.